224 A 5-Year Observational Study on Distal Femoral Periprosthetic Fractures in Elderly Patients in a Single Institution: Distal Femoral Replacement vs. Internal Fixation. (12th October 2021) - Ang, K L; Cheah, W; Jesani, H; Ooi, R; Agarwal, S
Abstract: Aim: To evaluate the outcome of distal femoral replacements versus internal fixation for elderly patients with distal femoral periprosthetic fracture in a single institution. Method: A five-year retrospective observational study was conducted of a consecutive series of patients with distal femoral periprosthetic fracture who underwent either distal femoral replacement (DFR) or internal fixation (IF) in a tertiary referral centre. Clinical information analysed included patient demographics, co-morbidities, interval between primary total knee arthroplasty (TKA) to distal femoral periprosthetic fracture, type of fracture, operative technique, preoperative ASA grade, post-operative complications, intensive therapy unit (ITU) stay, length of hospital stay (LOS), re-fixation and mortality. Results: Study included 27 patients of which fourteen patients underwent a DFR while 13 underwent an IF. 89% of the patients were females. Mean age of the patients at the time of fracture was 85 versus 80 (DFR vs IF). The mean interval from the primary TKA to the fracture were 80 months (range 0-181). There were no intraoperative complications in either group. Three patients required ITU stay from the DFR group while one patient from the IF group required re-fixation. Median LOS was 56 days (range 9-144) after DFR and 55 days (range 4-83) after IF. There was one 30-day mortality in the DFR group. One-year mortality for the DFR group was 7% vs 15% for the IF group. Conclusions: In our study, DFR and IF were observed to have similar LOS with a higher mortality in the IF group at one year. There was one re-fixation in the IF group.